Cancer Nanomedicine and Immune System—Interactions and Challenges - Ahmad, Suhana; Idris, Ros Akmal Mohd; Wan Hanaffi, Wan Nurhidayah; Perumal, Komathi; Boer, Jennifer C.; Plebanski, Magdalena; Jaafar, Juhana; Lim, Jit Kang; Mohamud, Rohimah (Frontiers in Nanotechnology, 2021)
Nanoparticles have tremendous therapeutic potential in the treatment of cancer as they increase drug delivery, attenuate drug toxicity, and protect drugs from rapid clearance. Since Doxil®, the first FDA-approved nanomedicine, several other cancer nanomedicines have been approved and have successfully increased the efficacy over their free drug counterparts. Although their mechanisms of action are well established, their effects towards our immune system, particularly in the tumor microenvironment (TME), still warrant further investigation. Herein, we review the interactions between an approved cancer nanomedicine with TME immunology. We also discuss the challenges that need to be addressed for the full clinical potential of ongoing cancer nanomedicines despite the encouraging preclinical data.